2018
DOI: 10.22201/fesz.23958723e.2019.1.142
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la capacidad de inhibición de hemólisis oxidativa y actividad antimicrobiana de fracciones peptídicas obtenidas de la hidrólisis de proteínas de huevo, leche y soya usando proteasas extraídas de Bromelia pinguin y Bromelia karatas

Abstract: Los hidrolizados proteínicos son una fuente de péptidos bioactivos (PB) y estos compuestos pueden ejercer un papel importante en la salud humana debido a sus diferentes acividades biológicas. El uso de proteasas de origen vegetal es una alternativa potencial para producir PB. El objetivo de este trabajo fue evaluar la capacidad de inhibición de la hemólisis oxidativa (IHO) y actividad antimicrobiana de hidrolizados y fracciones peptídicas obtenidas de la hidrólisis de proteínas de huevo (ovoalbúmina), leche y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The enzymes extracted from BP and BK show differences between their enzymatic activities, which coincide with what was previously reported by García-Magaña et al [30] (5.08 ± 0.70 for BK proteases and 43.58 ± 0.40 for BP proteases). BP proteases showed higher activity compared to BK proteases, this behavior is similar to the already reported by Aguilera-Aguirre et al [40] and Meza-Espinoza et al [25], and can be attributed to the presence of different types of cysteine proteases in both fruits [26,30,42]. In the same way, it has been reported that the different genetic characteristics of each fruit species synthesize endopeptidases with different structures and catalytic activities [25].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The enzymes extracted from BP and BK show differences between their enzymatic activities, which coincide with what was previously reported by García-Magaña et al [30] (5.08 ± 0.70 for BK proteases and 43.58 ± 0.40 for BP proteases). BP proteases showed higher activity compared to BK proteases, this behavior is similar to the already reported by Aguilera-Aguirre et al [40] and Meza-Espinoza et al [25], and can be attributed to the presence of different types of cysteine proteases in both fruits [26,30,42]. In the same way, it has been reported that the different genetic characteristics of each fruit species synthesize endopeptidases with different structures and catalytic activities [25].…”
Section: Discussionsupporting
confidence: 88%
“…The fruits of B. karatas and B. pinguin have been characterized as promising sources of plant proteases [25,[28][29][30]40]. One of the important points of this research is the incorporation of these plant enzymes in food technology processes and the obtaining of protein hydrolysates from food by-products and their comparison with a commercial plant enzyme (bromelain).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the highest activity was observed in B. pinguin proteases. In addition, the cytotoxic, anthelmintic and antimicrobial [3,6,7], anti-inflammatory [8] and antitumor [9] activities of the pre-purified extracts obtained from both fruits have also been studied [10,11]. Furthermore, it has been observed that they have shown remarkable thermal stability, as well as a high stability at high values of ionic strength (pI between 4.6 and 8.1) [3].…”
Section: Introductionmentioning
confidence: 99%